Men and Masculinity: A Philosophical Dialogue Approach (Concept: The Journal of Contemporary Community Education Practice Theory, 2023)
This article describes a project where philosophical dialogue was introduced to male community leaders to support them in a critical reflection on the meaning of masculinity. While it might seem unusual to apply an open-ended philosophical approach to a subject like masculinity, given its natural home in anthropological and sociological domains, this paper aims to show that the practice of philosophical dialogue provides a uniquely productive and fruitful way to engage men in discussion about masculinity.